Synthesis of wide bandgap Ga2O3 (Eg ∼ 4.6–4.7 eV) thin films on sapphire by low pressure chemical vapor deposition. Issue 4 (30th November 2015) - Rafique, Subrina; Han, Lu; Zhao, Hongping
Abstract : This paper presents the synthesis of wide bandgap Ga2 O3 thin films on differently oriented sapphire substrates by using low pressure chemical vapor deposition (LPCVD) technique. The effects of substrate orientation on the Ga2 O3 thin film surface morphology, crystal orientation, growth rate, and optical properties were studied. The Ga2 O3 thin films were synthesized on the c ‐plane (0001), a ‐plane (11−20), and r ‐plane (1−102) sapphire substrates using high purity metallic Ga and oxygen (O2 ) as source materials and argon (Ar) as carrier gas. The Ga2 O3 thin films grown on the c ‐plane and a ‐plane sapphire substrates are composed of pure β‐Ga2 O3 . A mixture of β‐Ga2 O3 and α‐Ga2 O3 phases is observed for the films grown on r ‐plane sapphire substrate. Well‐distinct transmission, absorption, and reflectance edge at E g  ∼ 4.6–4.7 eV are visible for all the films in the optical spectra measured in the spectral range from 200 to 800 nm.